Applying Fiscal Tools for Economic Development and Localization of CO VID‑ 19 Impacts on a Case Study of South America - E. Yu. Sidorova (Учёт. Анализ. Аудит, 2022)
The tax system of any country as a tool to fill the budget is never static, constantly subject to development and improvement, so it is relevant to study and apply its progressive elements used by different states. The subject of the study is the current tax transformation in Brazil, Argentina, Colombia, and its task is to study and apply its results, since the pandemic particularly affected the economies of developing countries. Countries of South America have been actively pursuing tax reforms since the middle of the last century, but localizing the effects of COVID‑19 requires tax changes in this area at the present time. The tax transformation in Brazil has involved a tax on dividends, capitalization of accumulated profits and dividends paid in kind, corporate income tax and corporate reorganizations. The tax transformation in Argentina also takes place in terms of income tax (restrictions on depreciation payments, permanent establishment), but there are also areas, such as tax haven policy, capital gains tax on non-residents of Argentina, and taxation of controlled foreign companies. The author carried the research on using general scientific methods of analysis, comparison, and deduction. The results of the study of tax transformation in South American countries can, considering the specifics of our economy, find practical implementation in the tax’s improvement system in the Russian Federation. Thus, it is proposed to adapt the following tax instruments in order to localize the effects of COVID‑19: tax loss carryforwards, deduction of R&D expenses.